THE DISTRIBUTION OF DIARRHEA AMONG THE ELDERLY IN THE WORKING AREA OF PERUMNAS PUBLIC HEALTH CENTER, KENDARI CITY, SOUTHEAST SULAWESI PROVINCE, IN 2020 – 2022 - Sitompul, Ria Lestari; Tosepu, Ramadhan; Prasetya, Fikki; Susanti, Sri (Universitas Halu Oleo, 2024)
The high incidence and mortality rate due to diarrhea is still a health problem in communities in developing countries such as Indonesia. Deaths due to diarrhea often occur in children or the elderly because those ages are vulnerable to dehydration. Diarrhea is also a problem in several areas in Southeast Sulawesi province, including in the working area of Perumnas Public Health Center. This research aimed to find out the distribution of diarrheal diseases in the working area of Perumnas Public Health Center in 2020 - 2022. The type of research was descriptive by examining secondary data that described or depicted the research object. The object or population in this research was all diarrhea sufferers registered in the working area of Perumnas Public Health Center, Kendari City, Southeast Sulawesi Province, in 2020 – 2022, totaling 63 sufferers. The sampling technique was carried out using total sampling. The variables in this study were the distribution of diarrhea based on age, gender, residence, education level, and occupation. The data was collected through medical records obtained from Perumnas Public Health Center, Kendari City Public, Southeast Sulawesi Province. The research result data was presented in the form of a distribution table of research results.This research can be concluded that there is an increase in cases of diarrhea in the elderly, are found at the age of 60-65 years, namely 52.2% with the highest frequency in men namely 60.9%, The education level of diarrhea sufferers in the elderly is highest, with a high school education level, namely 60.7% and the highest occupation being retired civil servants at 46.4%. Most cases come from Bende Village. Keywords: diarrhea, elderly, distribution, Perumnas Public Health Center